Comparison of vascular and non-vascular aquatic plant as indicators of cadmium toxicity - Kováčik, Jozef; Babula, Petr; Hedbavny, Josef (Chemosphere, 2017)
Antioxidative and microscopic responses in non-vascular (moss Taxiphyllum barbieri) and vascular (Ceratophyllum demersum) aquatic plants exposed to short-term (24 h) cadmium (Cd) excess (10 and 100 μM) were compared. Ceratophyllum considerably accumulated Cd but less pronounced symptoms of oxidative stress were detected by confocal microscopy (at the level of general ROS, hydrogen peroxide, hydroxyl radical/peroxynitrite and superoxide) that could be related to enhanced activities of antioxidative enzymes (SOD, CAT, APX). Amounts of ascorbic acid and non-protein thiols were higher in Ceratophyllum than in Taxiphyllum and increased with increasing Cd dose, which may help to better regulate circulation of free metal ions in Ceratophyllum mainly. Besides, it was observed that citric acid increased in Ceratophyllum while malic acid in Taxiphyllum in response to Cd which may also contribute to Cd chelation. Our data indicate that Ceratophyllum is a suitable species for Cd bioaccumulation while Taxiphyllum is more sensitive to Cd excess and thus suitable as indicator species. It was also proven that sensitive microscopic techniques allow the visualization of Cd-induced changes in aquatic plants even after short-term exposure when no morphological signs of damage are visible.
Keywords: Aquatic macrophyte; Oxidative Stress; Toxicity Tests; testy toxicity; oxidační stres; Magnoliopsida; Oxidative stress; Sulfhydryl Compounds; Ascorbic Acid; Heavy metals; Environmental Monitoring; Superoxide Dismutase; superoxiddismutasa; Antioxidants; Mosses; antioxidancia; kyselina askorbová; monitorování životního prostředí; Cadmium; kořeny rostlin; peroxid vodíku; kadmium; sulfhydrylové sloučeniny; Plant Roots; Hydrogen Peroxide